2018
DOI: 10.1021/acs.joc.7b03260
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Nitration of Protected Anilines

Abstract: The photocatalytic nitration of protected anilines proceeds with riboflavin tetraacetate as an organic photoredox catalyst. Sodium nitrite serves as the NO source in this visible-light-driven room temperature reaction. Various nitroanilines are obtained in moderate to good yields without the addition of acid or stoichiometric oxidation agents. The catalytic cycle is closed by aerial oxygen as the terminal oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 53 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…Although, the g e value obtained at the intervals of 3 min, 9 min, 15 min, 21 min, 27 min, 33 min were 2.0054, 2.0086, 2.0121, 2.0078, 2.0197 and none, respectively, there was still no reported reference to clarify the specific type of the free radicals. [20] Based on the findings and previous reports, [17,18] radical mechanism of the solid reaction was herein proposed as exemplified with the formation of 2 a (Scheme 4).…”
Section: Full Papersmentioning
confidence: 78%
See 2 more Smart Citations
“…Although, the g e value obtained at the intervals of 3 min, 9 min, 15 min, 21 min, 27 min, 33 min were 2.0054, 2.0086, 2.0121, 2.0078, 2.0197 and none, respectively, there was still no reported reference to clarify the specific type of the free radicals. [20] Based on the findings and previous reports, [17,18] radical mechanism of the solid reaction was herein proposed as exemplified with the formation of 2 a (Scheme 4).…”
Section: Full Papersmentioning
confidence: 78%
“…The investigation was continued in the absence of the catalysts, and exciting 70% of 2 a was successfully isolated under the transition metal-free conditions, with the assistance of PIFA in DCE at room temperature for 1 hour (entry 16). Other solvents, including MeCN, N,N-dimethyl formamide (DMF), dimethyl sulfoxide (DMSO), 1,4-dioxane, PEG-400 showed inferior performance to DCE did in the system (entries [16][17][18][19][20][21]. Surprisingly, exclusion of DCE, which meant the reaction mixture was grinded in mortar, improved the efficiency of the oxidative nitration reaction up to 78% within 30 min (entry 22, footnote c).…”
Section: Full Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in a seminal disclosure König et al accomplished visible‐light driven photo catalytic nitration of N ‐protected amine 57 using riboflavin tetraacetate (RFTA) as photoredox catalyst and NaNO 2 as the source of nitro‐group in air (Scheme ) . The protocol that encompassed a broad range of protected anilines, gave low yields of products or was unsuccessful for heterocyclic amines.…”
Section: Nano2 As Nitrating Agentmentioning
confidence: 99%
“…The presence of an electron-withdrawing group at α position to the carbonyl re- More recently, in a seminal disclosure König et al accomplished visible-light driven photo catalytic nitration of N-protected amine 57 using riboflavin tetraacetate (RFTA) as photoredox catalyst and NaNO 2 as the source of nitro-group in air (Scheme 47). [40] The protocol that encompassed a broad range of protected anilines, gave low yields of products or was unsuc- cessful for heterocyclic amines. It was suggested that the photocatalyst oxidizes the aniline leading to increase in acidity and consecutively formation of an amidyl radical LI by the loss of proton (Scheme 48).…”
Section: Nano 2 -Mediated Direct C-h Nitrationmentioning
confidence: 99%